Sobre linguagem, cognição e cérebro: Uma entrevista com Peter Hagoort - Bauer, Brigitte L.M; Mota, Mailce Borges (Revista da Anpoll, 2018)
Managing Director of the Max Planck Institute for Psycholinguistics, founding Director of the Donders Centre for Cognitive Neuroimaging (DCCN, 1999), and professor of Cognitive Neuroscience at Radboud University, all located in Nijmegen, the Netherlands, PETER HAGOORT examines how the brain controls language production and comprehension. He was one of the first to integrate psychological theory and models from neuroscience in an attempt to understand how the human language faculty is instantiated in the brain.